Linear groups saturated by subgroups of finite central dimension - Semko, Mykola Mykolaiovych; Skaskiv, Liliia Vasylivna; Yarova, Oksana Anatoliivna (Algebra and Discrete Mathematics, 2020)
Let F be a field, A be a vector space over F and G be a subgroup of GL(F, A). We say that G has a dense family of subgroups, having finite central dimension, if for every pair of subgroups H, K of G such that H 6 K and H is not maximal in K there exists a subgroup L of finite central dimension such that H 6 L 6 K. In this paper we study some locally soluble linear groups with a dense family of subgroups, having finite central dimension.

Нехай F — поле, A — векторний простір над F і G — підгрупа GL(F, A). Кажемо, що G має щільну сім’ю підгруп, що мають скінченну центральну розмірність, якщо для кожної пари підгрупи H, K групи G такі, що H 6 K і H не є максимальною в K існує підгрупа L скінченної центральної розмірності така що H 6 L 6 K. У цій статті ми вивчаємо деякі локально розв’язні лінійні групи з щільною сім'єю підгруп, що мають скінченний центральний ранг.
Keywords: field; vector space; groups; subgroups; finite central dimension; locally soluble linear groups; поле; векторний простір; групи; підгрупи; скінченна центральна розмірність; локально розв’язні лінійні групи